The Role of Academic Information Systems in Supporting Learning Effectiveness - Aprilya Christy Lorwens; Rudolf Kempa; Paul Arjanto (Publikasi Pendidikan, 2026)
ABSTRACTThis study aims to analyze the role of Academic Information Systems (AIS) in supporting learning effectiveness through student academic management in higher education. The research employed a quantitative survey design involving 85 respondents consisting of students, lecturers, and administrative staff at the Faculty of Teacher Training and Education, Universitas Pattimura. Data were collected using a questionnaire based on the End-User Computing Satisfaction (EUCS) model and supported by interviews. Data analysis was conducted using descriptive statistics and correlation techniques. The results indicate that AIS contributes positively to learning effectiveness by facilitating access to academic information, improving transparency of grades, and supporting monitoring of student progress. However, several constraints were identified, including limited system integration, delays in data updates, and variations in operator competence, which affect the quality of learning support. Approximately 58% of users reported difficulties in accessing certain system features, particularly during peak academic periods. These findings suggest that while AIS has improved academic service efficiency and supports learning processes, optimization of system performance and user competence is still required to enhance its effectiveness in higher education.